Subjective experiences of neurocognitive functioning in young people with major depression - Catherine Morey-Nase; Lisa J. Phillips; Shayden Bryce; Sarah Hetrick; Andrea L. Wright; Emma Caruana; Kelly Allott (BMC Psychiatry, 2019)
Abstract Background Research suggests that young people with major depressive disorder (MDD) experience neurocognitive deficits and that these are associated with poorer functional and clinical outcomes. However, we are yet to understand how young people experience such difficulties. The aim of the current study was to explore the subjective experiences of neurocognitive functioning among young people with MDD. Methods Semi-structured qualitative interviews were conducted with 11 young people (aged 17–24 years) attending a specialist clinic for youth experiencing moderate-severe depression. Interview transcripts were analysed via Thematic Analysis to identify patterns and themes representing how young people with MDD subjectively experience neurocognitive deficits. Results Five main themes were identified: (1) experience of neurocognitive complaints; (2) relationship between neurocognitive complaints and depression; (3) impact on functioning; (4) strategies and supports; and (5) neurocognitive complaints and treatment. Overall, young people with MDD commonly experienced a range of subjective neurocognitive complaints. These appeared to have a bidirectional relationship with depressive symptomatology and significantly disrupted vocational, social and independent functioning, and aspects of psychological well-being including self-esteem. Neurocognitive difficulties represented an experiential barrier to psychological therapeutic engagement and were perceived as variably responsive to psychotropic medications, highlighting the need for targeted intervention. Discussion Neurocognitive difficulties are a common and pervasive experience for young people with MDD, with perceived impacts on depressive symptoms, attitudinal beliefs, everyday functioning and therapeutic engagement. Subjective neurocognitive complaints may therefore contribute to or exacerbate personal challenges faced by young people with MDD and thus, require early identification, consideration in psychological formulation, and treatment. Further research into the mechanisms of neurocognitive impairment in MDD is also needed.